2015
DOI: 10.1111/jep.12451
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported post‐operative recovery in children: development of an instrument

Abstract: Rationale, aims, and objectives: According the United Nations (1989), children have the right to be heard and to have their opinions respected. Since postoperative recovery is an individual and subjective experience and patient-reported outcome measures are considered important, our aim was to develop and test an instrument to measure self-reported quality of recovery in children after surgical procedures.Methods: Development of the instrument Postoperative Recovery in Children (PRiC) was influenced by Quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 36 publications
0
31
1
Order By: Relevance
“…In contrast to other studies that targeted parental satisfaction, PRiC is a patient‐reported instrument that was developed to evaluate the quality of recovery from a child's perspective. The response rate for PRiC, however, was about 61%, and 76% of the children did not answer the survey themselves . The modified APS‐POQ‐R in this study was intended for parents because a child's willingness to participate in a survey may be influenced by the feeling of lethargy, hunger, and pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to other studies that targeted parental satisfaction, PRiC is a patient‐reported instrument that was developed to evaluate the quality of recovery from a child's perspective. The response rate for PRiC, however, was about 61%, and 76% of the children did not answer the survey themselves . The modified APS‐POQ‐R in this study was intended for parents because a child's willingness to participate in a survey may be influenced by the feeling of lethargy, hunger, and pain.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome measures that constitute the success of postoperative care form an important research question that is relevant to our anesthetic practice. Focusing on pediatric patients, Bramhagen et al developed and validated an instrument, the Postoperative Recovery in Children (PRiC), that was influenced by the modified Quality of Recovery‐40 used for the adults . Compared to the questionnaire in our study, the PRiC focused on the different aspects of recovery from anesthesia, specifically for tonsil surgery in children.…”
Section: Discussionmentioning
confidence: 99%
“…Some efforts have been made to develop measures for children's participation, but the available questionnaires and instruments are neither based on the child perspective on participation nor adapted to general health care. The available instruments are instead specifically designed for use in a school setting (Davies, Soon, Young, & Clausen‐Yamaki, ; Simeonsson, Carlson, Huntington, McMillen, & Brent, ), in the community (Washington, Wilson, Engel, & Jensen, ), mixed contexts (Bedell & Dumas, ; Chien, Rodger, & Copley, ; Coster et al, ; Khetani, Graham, Davies, Law, & Simeonsson, ; Kramer et al, ; Michelsen et al, ) or a very specific circumstance, such as having a disability (Chien et al, ; Michelsen et al, ; Noreau et al, ; Timmons & Wagner, ; Washington et al, ) or postoperative care (Bramhagen et al, ). The questions used in these instruments focus on everyday tasks (Coster et al, , ; King et al, ; Mishra & Rangasayee, ; Noreau et al, ), symptoms and pain (Bramhagen et al, ; File S1).…”
Section: Introductionmentioning
confidence: 99%
“…It is adapted to be inserted in a mobile app called Recovery Assessment by Phone Points . The initial version of SwQoR developed in 2014 included 31 items inspired by different instruments measuring postoperative recovery . A flow chart of SwQoR development is given in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The initial version of SwQoR developed in 2014 included 31 items 10 inspired by different instruments measuring postoperative recovery. [13][14][15][16][17][18] A flow chart of SwQoR development is given in Figure 1. SwQoR includes both positive items (n = 13) such as having a general feeling of well-being and negative items (n = 18) such as postoperative pain; the positive items are presented first, followed by the negative items.…”
Section: Introductionmentioning
confidence: 99%